Processo de Moran em Grafos Evolutivos e o Teorema de Perron-Frobenius - Ciciliotti, Diogo Taylor (2022)
In this work, we shall present some of the most important results related to the (simple) Moran Process - a discrete-time Markov chain - and the fixation probability of a mutant gene as a result of the Perron-Frobenius Theorem. In addition, we will generalize the model populational structure, labeling the individuals in directed graphs and highlighting populational structures that act as natural selection suppressors or natural selection amplifiers.